Multi-omics reveals Dengzhan Shengmai formulation ameliorates cognitive impairments in D-galactose-induced aging mouse model by regulating CXCL12/CXCR4 and gut microbiota - Hou, Jing-Yi; Xu, He; Cao, Guang-Zhao; Tian, Liang-Liang; Wang, Li-Han; Zhu, Nai-Qiang; Zhang, Jing-Jing; Yang, Hong-Jun (Frontiers in Pharmacology, 2023)
Dengzhan Shengmai (DZSM), a traditional Chinese medicine formulation, has been administrated extensively for cognitively impaired elderly individuals. However, the underlying mechanism of improvement of the cognitive impairment (CI) by DZSM remains unknown. This study aimed to elucidate the underlying mechanism of the effect of DZSM on aging-associated CI via a comprehensive combination of transcriptomics and microbiota assessment. DZSM was orally administered to D-galactose¬-induced aging mouse model, and evaluation with an open field task (OFT), Morris water maze (MWM), and histopathological staining was performed. Transcriptomics and 16S rDNA sequencing were applied to elucidate the mechanism of DZSM in alleviating cognitive deficits, and an enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (PCR), and immunofluorescence were employed to verify the results. The results first confirmed the therapeutic effects of DZSM on protecting against cognitive defects; specifically, DZSM improved learning and impairment, suppressed neuro loss, and increased Nissl body morphology repair. Comprehensive integrated transcriptomics and microbiota analysis indicated that chemokine CXC motif receptor 4 (CXCR4) and its ligand CXC chemokine ligand 12 (CXCL12) were targets for improving cognitive impairments with DZSM and also indirectly suppressed the intestinal flora composition. Furthermore, in vivo results confirmed that DZSM suppressed the expression of CXCR4, CXCL12, and inflammatory cytokines. This suggested that DZSM inhibited CXCL12/CXCR4 expression and modulated intestinal microbiome composition by influencing inflammatory factors. DZSM improves aging-related CI effects via decreased CXCL12/CXCR4 and inflammatory factor modulation to improve the gut microbiota composition.